Metal-organic-framework derived Co-Pd bond is preferred over Fe-Pd for reductive upgrading of furfural to tetrahydrofurfuryl alcohol - Pendem, Saikiran; Bolla, Srinivasa Rao; Morgan, David J; Shinde, Digambar B; Lai, Zhiping; Nakka, Lingaiah; Mondal, John (Dalton transactions : an international journal of inorganic chemistry, 2019)
Combined noble-transition metal catalysts have been used to produce a wide range of important non-petroleum-based chemicals from biomass-derived furfural (as a platform molecule) and have garnered colossal research interest due to the urgent demand for sustainable and clean fuels. Herein, we report the palladium-modified metal-organic-framework (MOF) assisted preparation of PdCo 3 O 4 and PdFe 3 O 4 nanoparticles encapsulated in a graphitic N-doped carbon (NC) matrix via facile in situ thermolysis. This provides a change in selectivity with superior catalytic activity for the reductive upgrading of biomass-derived furfural (FA). Under the optimized reaction conditions, the newly designed PdCo 3 O 4 @NC catalyst exhibited highly efficient catalytic performance in the hydrogenation of furfural, providing 100% furfural conversion with 95% yield of tetrahydrofurfuryl alcohol (THFAL). In contrast, the as-synthesized Pd-Fe 3 O 4 @NC afforded a THFAL yield of 70% after an 8 h reaction with four consecutive recycling tests. Based on different characterization data (XPS, H 2 -TPR) for nanohybrids, we can conclude that the presence of PdCo-N x active sites, and the multiple synergistic effects between Co 3 O 4 and Pd( ii ), Co 3 O 4 and Pd 0 , as well as the presence of N in the carbonaceous matrix, are responsible for the superior catalytic activity and improved catalyst stability. Our strategy provides a facile design and synthesis process for a noble-transition metal alloy as a superior biomass refining, robust catalyst via noble metal modified MOFs as precursors. The metal-organic-framework-derived Co-Pd bond can more efficiently catalyze the reductive upgrading of furfural to tetrahydrofurfuryl alcohol production as compared to the Fe-Pd bond.